Sintesis Bio-Pelumas Dari Minyak Limbah Ikan Patin Dengan Pengaruh Kecepatan Pengadukan Dan Suhu Reaksi - Amril, Ari Ridha; Irdoni, Irdoni; Nirwana, Nirwana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bio-lubricant synthesis from catfish waste oil is purposed to modify the useless oil to be a bio-lubricant. That function’s is to protect the engine component from wear. Esterification with ethylene glycol toward acid from catfish waste oil hydrolysis with mole ratio 1:4 for 4 hours, with variation of temperature and mixing speed. The waste extracted by rendering, oil’s boiling point is 270oC, the viscosity is 15,69 mPa s. The oil hydrolyzed at 80 oC with adding of HCl concentrated catalyst 0,1% weight/weight for 8 hours and produce the acid. That’s polymerized by adding benzoyl peroxide as 0,2% for 5 hours at 120 oC. Then, polyestherification by adding ethylene glycol in mole ratios of 1:4, for 4 hours at 120 oC, 150 oC, 1800C, and mixing speed at 150 rpm, 180 rpm, and 210 rpm. The resulting has its density, it’s 0,942 gr/m, viscosity is 61,081 mPa.s, flame point is 290,5oC, boiling point is 290 oC with yield of 66,5%. The product has a commercial standard (density is 0,92 gr/ml and viscosity is >41,1 mPa.s). The best result from this research was obtained by mole ratio 1:4 for 4 hours; the mixing speed is 150 rpm at 150oC.Keyword: bio-lubricant, oil of catfish waste